Privacy and confidentiality: perspectives of mental health consumers and carers in pharmacy settings - Hattingh, H. Laetitia; Knox, K.; Fejzic, J.; McConnell, D.; Fowler, J.; Mey, A.; Kelly, F.; Wheeler, A. (John Wiley & Sons Ltd, 2015)
Objectives - The study aims to explore within the community pharmacy practice context the views of mental health stakeholders on: (1) current and past experiences of privacy, confidentiality and support; and (2) expectations and needs in relation to privacy and confidentiality. Methods - In-depth interviews and focus groups were conducted in three states in Australia, namely Queensland, the northern region of New South Wales and Western Australia, between December 2011 and March 2012. Key findings - There were 98 participants consisting of consumers and carers (n=74), health professionals (n=13) and representatives from consumer organisations (n=11). Participants highlighted a need for improved staff awareness. Consumers indicated a desire to receive information in a way that respects their privacy and confidentiality, in an appropriate space. Areas identified that require improved protection of privacy and confidentiality during pharmacy interactions were the number of staff having access to sensitive information, workflow models causing information exposure and pharmacies' layout not facilitating private discussions. Challenges experienced by carers created feelings of isolation which could impact on care. Conclusions - This study explored mental health stakeholders' experiences and expectations regarding privacy and confidentiality in the Australian community pharmacy context. A need for better pharmacy staff training about the importance of privacy and confidentiality and strategies to enhance compliance with national pharmacy practice requirements was identified. Findings provided insight into privacy and confidentiality needs and will assist in the development of pharmacy staff training material to better support consumers with sensitive conditions.